Christian Temporalities Living Between the Already Fulfilled and the Not Yet Completed - Hermkens, Anna-Karina; Coleman, Simon; Tomlinson, Matt (Contemporary Anthropology of Religion, 2024)
XIII, 237 p. 2 illus.